Propuesta de mejora del servicio de hospedaje en el Hotel Maracos utilizando Lean Service. (2021)
The research was carried out at the Maracos Hotel in the city of Villavicencio, for the reactivation of the hotel an improvement plan has been proposed to generate attraction and customer loyalty through the Lean Service methodology and other tools such as the QFD and VSM house of quality, through these two tools it was possible to know the process of the lodging service, the perception that customers have of it and the waste, factors such as minimum demand, improve customer service and unestablished processes; The Kaizen tool was chosen to establish the procedures since it is used for continuous improvement and several activities were established to improve the lodging service, including standardizing the cleaning service in the rooms, training personnel on the importance of customer service and establishing a publicity plan to increase demand, An Ideal VSM of the proposed improvement plan was carried out and its financial viability was evaluated using the benefit-cost tool, which resulted in viability, since the economic benefits are greater than the cost of the improvement plan.